Synthesis of dihydrogen phosphate-based ionic liquids: Experimental and COSMO-RS based investigation for methane hydrate inhibition - Sulaimon, A.A. (Elsevier B.V., 2020)
In this study, three novel ionic liquids (ILs) having dihydrogen phosphate anion namely, 1-ethyl-3-methylimidazolium dihydrogen phosphate (EMIMDHP), 1-(3-cyanopropyl)-3-methylimidazolium dihydrogen phosphate (CPMIM DHP) and 1-butyl-3-methylimidazolium dihydrogen phosphate (BMIM DHP) are synthesized through metathesis reaction for their potential application as novel gas hydrate inhibitors. Their structures are confirmed by Nuclear Magnetic Resonance (1H NMR). The ILs effects on the equilibrium methane hydrate dissociation curve and the induction time in a pressure range of 50 to 100 bar are measured in a high-pressure micro-differential scanning calorimeter (HP Micro-DSC). The inhibition ability of these ILs towards hydrate formation are predicted through the analysis of Ï-profile, which describe the hydrogen-bond formation properties of the ILs, computed by COSMO-RS software. Prior to that, a standard correlation model for hydrate dissociation of pure water as the baseline for the Hydrate-aqueous Liquid-Vapor Equilibrium (HLVE) curve is successfully developed through experimental and literature data. Hence, this model can be used by any researcher as a baseline for the HLVE curve. Through the Micro-DSC experiments, these ILs are found to perform a dual-functional thermodynamic and kinetic inhibitor behaviour. These ILs simultaneously shift the HLVE curve to a lower temperature and retard the hydrate formation by slowing down the hydrate nucleation rate. Â© 2020 Elsevier B.V.